Intestinal necrosis cannot be neglected in a patient with hepatic portal vein gas combined with appendicitis: a rare case report and literature review - Haimin Chen; Qingsong Wu; Hongcai Fang; Bo Liang; Lu Fang (BMC Surgery, 2019)
Abstract Background Hepatic portal vein gas (HPVG) is a rare acute abdomen, which is not an independent disease. Meanwhile, HPVG combined with appendicitis has been rarely reported. We found only a similar report by looking for literature, but no intestinal necrosis occurred. We report a patient with HPVG, appendicitis and intestinal necrosis was reported in the current study. The patient was given frequent monitoring and had been conducted operation in time. Case presentation An 86-year-old female with appendicitis complicated by HPVG was reported in the present study. Abdominal examination revealed rebound tenderness at the McBurney’s point. Moreover, abdominal computed tomography (CT) revealed gas in portal and mesenteric veins in addition to appendicitis. An emergency operation was planned on the appendix. However, the patient refused surgical treatment. Therefore, conservative treatment of antibiotics and frequent imaging observation was conducted for this patient. Although imaging results suggested disappeared gas in intra- and extra-hepatic portal veins, the small intestine was dilated, after conservative treatment of antibiotics. In addition, signs of diffused peritonitis could also be observed and an exploratory laparotomy was performed. Intra-operative findings had confirmed suppurated appendix, mesenteric ischemia and small intestinal necrosis. Conclusions Frequent monitoring benefits us in observing the progress of intestinal diseases. When there exist other possible causes of HPVG such as infection, it is not easy for us to ignore the possibility of intestinal necrosis.